Linking Universities to Communities. - Flores, Cecilia.; Jackson, Trina.; Merrill, Drew.; Ortiz, Miriam. (Tufts University. Tisch Library., 2018)
Students in UEP 261 Community Development, Planning and Politics (Spring 2018, Professor Lorlene Hoyt) worked together to create a video project to "secure funding to promote radical change in academia through meaningful partnerships between universities and the communities with whom they engage." The video appeared on the Tufts Crowdfunding platform in April 2018. To read more about how students Cecilia Flores, Trina Jackson, Drew Merrill, Miriam Ortiz, Professor Hoyt, and Talloires Network Program Administrator Brianda Hernandez Cavalcanti describe their project, visit the archived version of the Tufts Crowdfunding page at: https://perma.cc/6X8P-FTCK.